Understanding type 1 diabetes through proteomics. (3rd July 2017) - Crèvecoeur, Inne; Vig, Saurabh; Mathieu, Chantal; Overbergh, Lut
ABSTRACT: Introduction : Auto-immunity against pancreatic beta-cells leads to an absolute shortage of the hormone insulin, resulting in hyperglycemia and the onset of type 1 diabetes (T1D). Proteomic approaches have been used to elucidate the mechanisms of beta-cell dysfunction and death. Areas covered : In the present review, we discuss discoveries in the beta-cell proteome that have contributed to better insights in the role of the beta-cell in T1D. Techniques, such as 2D-DIGE and MALDI imaging, together with new approaches for sample preparation, including laser capture microdissection and immunopeptidomics, have resulted in novel mechanistic insights in the pathogenesis of T1D. We describe how proteomic studies in beta-cell lines as well as isolated islets from animal models and humans have discovered intracellular signaling pathways leading to beta-cell destruction, the generation of neo-antigens through post-translational modifications of beta-cell antigens as well as better biomarkers of disease progression. Expert commentary : Proteomics has contributed to the discovery of beta-cell neo-autoantigen generation through post-translational modifications, hybrid insulin peptide formation and the generation of defective ribosomal gene products. These concepts are revolutionizing our insights in the pathogenesis of T1D, acknowledging a central role for the beta-cell in its own destruction.